(3cJGH JVef PcQ eQGJH GdfGS aj GdUHQ hGdQVi YfO fRhd GdHdGjG Hges
(3ChdgG (B:s
(3GdMeO ddg hMOg hbO HdZfi cJGHce hGfJe JPcQhf ajg eSFdI GdUHQ Ydi GdHdGA hCfce ENJdaJe ajgG s
(3BNQgG (B:s
(3hdjS GdRjGOGJ Gdjbjf fgGjI cdeG JagehG hJabghG ai GdOjf EROGOhG jbjfkG Ydi jbjf QRbfG Gddg efg GdMX hGdGLQ Hefg hcQeg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdESchQjGd s
Keywords: (3Gdabg GdESdGejs